The Social Structure of Insiders and Outsiders: Toward a Network Community Perspective on Firm Performance - Wu, Xiaoteng; Adbi, Arzi; Mahmood, Ishtiaq Pasha (Academy of Management Journal, 2024)
Management literature on how interorganizational relationships influence firm performance has emphasized the importance of connections, positions, and cliques. We advance this literature by examining how network communities (membership in cohesive network structures) shape the performance of venture capital (VC) firms. We propose that community insiders affiliated with at least one network community will outperform outsiders. We also explicate the conditions under which the advantages of network community affiliations are likely to be muted. Specifically, we argue for the potential diseconomies of network community affiliations and the possibility of a substitutive relationship between network communities and institutional development. Leveraging recent advances in community-detection technology and longitudinal data on VC firms in China, we find support for our theoretical arguments. Analysis of mechanisms underlying our theoretical arguments reveals that the value of community affiliations comes from indirect connections within network communities. By integrating social network and institutional perspectives, this study highlights not only the promises but also the limits of relying on network community affiliations.